1998
DOI: 10.3759/tropics.7.195
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of Dipterocarp Species Using Nucleotide Sequences of Two Non-coding Regions in Chloroplast DNA.

Abstract: A total of 53 dipterocarp species belonging to ten genera were studied to examine phylogenetic relationships using the sequences of iwo non-coding regions in chloroplast DNA. Richetioides. The genera Shorea and Hopea werc more divergenl than the other genera. These resulls suggest that they are the groups of phylogenetically more diversified species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 11 publications
8
30
0
Order By: Relevance
“…The generic relationships revealed by our NJ tree are mostly in agreement with previous molecular phylogenies based on cpDNA Gamage et al, 2003;Kajita et al, 1998;Kamiya et al, 1998). However, our current results provide new evidence regarding the relationships of additional genera such as Monotes, Vateriopsis and Stemonoporus, which were not included or discussed well (except Monotes) in most previous studies Kamiya et al, 1998).…”
Section: Generic Relationshipssupporting
confidence: 80%
See 3 more Smart Citations
“…The generic relationships revealed by our NJ tree are mostly in agreement with previous molecular phylogenies based on cpDNA Gamage et al, 2003;Kajita et al, 1998;Kamiya et al, 1998). However, our current results provide new evidence regarding the relationships of additional genera such as Monotes, Vateriopsis and Stemonoporus, which were not included or discussed well (except Monotes) in most previous studies Kamiya et al, 1998).…”
Section: Generic Relationshipssupporting
confidence: 80%
“…Since then, several other phylogenetic studies on Dipterocarpaceae were reported based on chloroplast (cp) DNA sequences Gamage et al, 2003;Kajita et al, 1998;Kamiya et al, 1998;Morton et al, 1999) and the nuclear gene PgiC (Kamiya et al, 2005). However, previous studies on molecular phylogeny of the Dipterocarpaceae included either limited number of species Morton et al, 1999;Tsumura et al, 1996) or informative sites (Gamage et al, 2003;Kamiya et al, 1998) or both . The most recent work by Kamiya et al (2005) has mainly focused on the relationships of Shorea , Hopea, Neobalanocarpus and Parashorea genera and did not include species from the Dipterocarpeae tribe and species of the Doona genus (Kostermans, 1984;Kostermans, 1992;Maury, 1978;Maury-Lechon, 1979).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of this study will be used for effective management of biodieversity resources. The genetic variation and genetic relationships of tree populations in Sarawak using molecular markers, such as RAPD, AFLP, microsatellite and DNA sequencing were studied (Harada et al, 1994;Kamiya et al, 1998 of organisms, the genetic constitution of tree populations could be objectivity determined if proper molecular makers are used, that is, the analysis of DNA variations could provide more conclusive results for studies on phylogeny and population genetics of organisms, than indirect observation of genetic variation using morphology and proteins (Nei, 1987). Moreover, it is also mentioned that because much of the research today uses PCR (polymerase chain reaction) DNA material should be qualified for the method (Mullis & Faloona, 1987).…”
Section: Introductionmentioning
confidence: 99%